2013
DOI: 10.1089/scd.2012.0150
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Receptors in Human Embryonic Stem Cell Neurodifferentiation

Abstract: We tested whether dopaminergic drugs can improve the protocol for in vitro differentiation of H9 human embryonic stem cells (hESCs) into dopaminergic neurons. The expression of 5 dopamine (DA) receptor subtypes (mRNA and protein) was analyzed at each protocol stage (1, undifferentiated hESCs; 2, embryoid bodies [EBs]; 3, neuroepithelial rosettes; 4, expanding neuroepithelium; and 5, differentiating neurons) and compared to human fetal brain (gestational week 17-19). D2-like DA receptors (D2, D3, and D4) predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 68 publications
2
13
0
Order By: Relevance
“…Whereas the presence of D2-like DA receptors was shown in the human embryonic stem cells (Belinsky et al, 2013), cocaineinduced dysfunction of DA receptor signalling lead to abnormal differentiation of cerebral cortical neurons in rabbits (Jones et al, 2000). Reimer et al (2013) demonstrated that dopaminergic signal was essential during neurogenesis in the zebrafish D. rerio.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the presence of D2-like DA receptors was shown in the human embryonic stem cells (Belinsky et al, 2013), cocaineinduced dysfunction of DA receptor signalling lead to abnormal differentiation of cerebral cortical neurons in rabbits (Jones et al, 2000). Reimer et al (2013) demonstrated that dopaminergic signal was essential during neurogenesis in the zebrafish D. rerio.…”
Section: Discussionmentioning
confidence: 99%
“…MSX1 seems to be an active gene in the HES cells as implicated by its up-regulated expression when the HES cells are co-cultured with PA6 cells [ 37 ], and, conversely, the expression levels of MSX1 become lower when the HES cells are treated with dopamine [ 38 ]. In a genome-wide methylation-gene expression study between the epigenetic modifications of retinoic acid treated and undifferentiated HES cells, the author uncovered 166 differentially methylated CpG sites and 2,013 differentially expressed genes, in which 19 genes including MSX1 are highly correlated with each other [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…While cells and tissues differentiated from PSCs have been widely used for calcium signaling studies, we found only a limited number of data about such signaling in pluripotent stem cells, and even these data are mainly from mouse cell studies. Calcium signals in hESC-derived cardiomyocytes and neural cell types have been measured in most cases by calcium sensitive dyes: for cardiomyocytes Fura-2/AM [25][26][27][28], Fluo-4/AM [29,30] or dsRed+ [27], while for neural cell types Fluo-3/AM [8,31] Fura-2/AM [8,32] or Oregon green 488 Bapta-1 AM [33] have been applied. In pluripotent cells the application of Fluo-3/AM (mESC- [34], hESC- [8]) or Fluo-4/AM (mESC- [35][36][37], and hESC [12]) has been reported.…”
Section: Methods For Studying Calcium Signals In Human Ps Cellsmentioning
confidence: 99%